Promoting the Culture of Legal Entrepreneurship: The Fundamental Role of Universities in the Post-conflict Phase - Paredes Bustamante, Martha Lucía (DIXI, 2017)
Introduction: The dynamics of globalization in the contemporary world and the outlook of the current Colombian reality—the peace dialogs, reaching an agreement to end an over-50-year conflict, and the subsequent post-conflict phase—demand that universities, their managers, professors, and graduates deploy and plan a series of programs and actions to bind higher education institutions to social and labor problems from little-explored dimensions, such as legal entrepreneurship. Methods: The project explores new possibilities to practice law and train lawyers to apply their legal knowledge in detecting opportunities to design solutions to problems in contexts of conflict with precarious rates of unemployment, health, education, and coexistence. Results and conclusions: This exploration on novel applications of legal knowledge will allow to establish whether the law professor and student can walk through little-ex-plored fields—professional practices of an entrepreneurial behavior, in this case—,by formulating an idea that can be translated into innovative projects; comply with ethical values and constitutional principles in contexts of peace and conflict; and take on the commitment and historical behavior of a managing lawyer required by the 21st century, who is oriented to “know law and towards a new know-how with the knowledge of law.”